Analysis of Cash Waqf Literacy Level: A Study on Banjarmasin State Polytechnic - Mairijani, Mairijani; Nurhidayati, Nurhidayati; Lathifah, Auliya (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2024)
The development of productive waqf in educational institutions has now extended to higher education institutions, including Institut Pertanian Bogor (IPB). IPB’s waqf agency, known as the Business, Investment, and Waqf Management Body, has successfully developed, collected, and distributed waqf funds to educational institutions and their students. Therefore, as an effort to replicate this success, this study aims to analyze the level of cash waqf literacy among the academic community of State Polytechnic of Banjarmasin. This study employs a descriptive quantitative research design with proportional random sampling as the sampling technique. This technique ensures that all members have an equal chance of being selected as samples according to their proportion, resulting in a total of 80 samples. The arrangement of indicators follows the Zakat Literacy Index concept developed by Puskas BAZNAS. A Likert scale questionnaire is used as the research instrument, while the Chen and Volp literacy level scale is applied to categorize cash waqf literacy levels. The results of this study indicate that the cash waqf literacy index among the academic community of Banjarmasin State Polytechnic, which includes lecturers, education administrators, and lab assistants, is 80.00%, placing it in the intermediate category.